Application of the Qowaid and Tarjamah Methods, Contextual Teaching and Learning Strategies to Improve the Writing Skills Students Class XI |تطبيق طريقة القواعد والترجمة واستراتيجية الدراسات والتدريس السياقي لترقية مهارة الكتابة لدى طلبة الصف الحادى عشر بمدرسة العالية الإسلامية - Khairunnisa, Auliya; Hijriyah, Umi; Erlina; Kusuma, Guntur Cahaya; Choirunnisa, Nur Wahidah (NAJAH BESTARI, 2024)
The Qawaid wa Tarjamah method is an Arabic language learning method that emphasizes aspects of grammar and the translation of Arabic texts into the target language. This method is a classic method that has been around for a long time, especially widely used on the European continent in learning Latin and Greek. Along with the rapid development of science and technology and the many new methods in the industrial era 5.0, Arabic language teachers only use the Qawaid wa tarjamah method when needed and also adapt it to the needs of students, especially in teaching Arabic grammar such as nahwu and shorof rules. This means that this method is still needed and still relevant today. Therefore, this method needs to be modified with current strategies. One strategy that can be combined with this method is the Contextual Teaching and Learning strategy or commonly known as CTL. Integrating the Qawaid wa tarjamah method with the CTL strategy will create learning that is more communicative and applicable, especially in Maharah Kitabah. For example, in learning the fi'liyah number rules, it is first applied using the CTL strategy by presenting examples that are already known to students, then explained in detail regarding the complete rules using the Qawaid wa Tarjamah method to better understand students. with these methods and strategies the results of the study showed that students' writing skills increased.